Important Functions and Molecular Mechanisms of Mitochondrial Redox Signaling in Pulmonary Hypertension - Jorge Reyes-García; Abril Carbajal-García; Annarita Di Mise; Yun-Min Zheng; Xiangdong Wang; Yong-Xiao Wang (MDPI AG, 2022)
Mitochondria are important organelles that act as a primary site to produce reactive oxygen species (ROS). Additionally, mitochondria play a pivotal role in the regulation of Ca2+ signaling, fatty acid oxidation, and ketone synthesis. Dysfunction of these signaling molecules leads to the development of pulmonary hypertension (PH), atherosclerosis, and other vascular diseases. Features of PH include vasoconstriction and pulmonary artery (PA) remodeling, which can result from abnormal proliferation, apoptosis, and migration of PA smooth muscle cells (PASMCs). These responses are mediated by increased Rieske iron-sulfur protein (RISP)-dependent mitochondrial ROS production and increased mitochondrial Ca2+ levels. Mitochondrial ROS and Ca2+ can both synergistically activate nuclear factor κB (NF-κB) to trigger inflammatory responses leading to PH, right ventricular failure, and death. Evidence suggests that increased mitochondrial ROS and Ca2+ signaling leads to abnormal synthesis of ketones, which play a critical role in the development of PH. In this review, we discuss some of the recent findings on the important interactive role and molecular mechanisms of mitochondrial ROS and Ca2+ in the development and progression of PH. We also address the contributions of NF-κB-dependent inflammatory responses and ketone-mediated oxidative stress due to abnormal regulation of mitochondrial ROS and Ca2+ signaling in PH.